2019
DOI: 10.1136/bmjopen-2019-029173
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how to enhance efficacy and effectiveness of feedback via e-portfolio: a realist synthesis protocol

Abstract: IntroductionThe validity of feedback as one of the defining components for electronic portfolios (e-portfolios) to be effective and efficacious has yet to be demonstrated. While the literature has shown individual beneficial features of e-portfolios and feedback per se, evidence of feedback as mediated through technology directly resulting in improved educational practice is scarce. The explanation of how feedback via e-portfolio improves educational practice is particularly vague.Methods and analysisThe aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The electronic portfolio (e-portfolio) is a form of MSP that is hosted on electronic platforms 5 , 6 , 9 , 47 , 53 , 56 , 58 , 61 , 63 , and may be created using unique software 47 , 63 , 65 , 76 , 86 . Compared to hardcopy portfolios, they are more durable 66 , user friendly 63 , 75 , 77 , accessible 6 , 53 , 58 , 61 , 80 collaborative 5 , 67 , 73 , 76 , 81 and superior for assessment in certain areas 61 . Furthermore, they are able to include a wider variety of evidence including videos or website links 5 , 63 , 75 , 78 , 79 , provide increased privacy and confidentiality for users including students and coaches 67 , 73 , 86 and allow for instant comparison between students 76 .…”
Section: Resultsmentioning
confidence: 99%
“…The electronic portfolio (e-portfolio) is a form of MSP that is hosted on electronic platforms 5 , 6 , 9 , 47 , 53 , 56 , 58 , 61 , 63 , and may be created using unique software 47 , 63 , 65 , 76 , 86 . Compared to hardcopy portfolios, they are more durable 66 , user friendly 63 , 75 , 77 , accessible 6 , 53 , 58 , 61 , 80 collaborative 5 , 67 , 73 , 76 , 81 and superior for assessment in certain areas 61 . Furthermore, they are able to include a wider variety of evidence including videos or website links 5 , 63 , 75 , 78 , 79 , provide increased privacy and confidentiality for users including students and coaches 67 , 73 , 86 and allow for instant comparison between students 76 .…”
Section: Resultsmentioning
confidence: 99%
“…An E-portfolio is believed to be able to improve the soft skills of students, foster critical thinking patterns in solving a problem and help them in independent learning and continuous learning processes. This is also supported by several experts who state that the e-portfolio helps students independently in designing effective learning for themselves and future learning goals related to their careers after graduation (Klenowski et al, 2006); (Gülbahar & Tinmaz, 2006); (Bolliger & Shepherd, 2010); (Huang et al, 2011); (Cepik & Yastibas, 2013); (Nurhayati & Sumbawati, 2014); (Wetcho & Na-Songkhla, 2019); (Babovič et al, 2019).…”
Section: Introductionmentioning
confidence: 83%
“…This study follows the iterative steps suggested by Pawson et al 28 and implemented in previous reviews undertaken by the lead author. 31 32 We plan to report our realist syntheses according to RAMESES publication standards. 33 This synthesis work will facilitate our development of an initial programme theory in which we will hypothesise the intended outcomes of the programme and the proposed mechanisms that bring forth those outcomes, alongside the various contexts in which we believe these to occur.…”
Section: Methodsmentioning
confidence: 99%